Geodesic deviation equation in f (R) gravity - Guarnizo, Alejandro; Castaneda, Leonardo; Tejeiro-Sarmiento, Juan-Manuel (General relativity and gravitation, 2011)
In this paper we study the Geodesic Deviation Equation (GDE) in metric f (R) gravity. We start giving a brief introduction of the GDE in General Relativity in the case of the standard cosmology. Next we generalize the GDE for metric f (R) gravity using again the FLRW metric. A generalization of the Mattig relation is also obtained. Finally we give and equivalent expression to the Dyer-Roeder equation in General Relativity in the context of f (R) gravity.